Hubungan sikap pembelajaran dengan pencapaian Matematik di IKM - Norzilawati, Yusof (2009)
The purpose of the study is to identify the differentiation between learning behaviour in Mathematics (based on interest, motivation and expectation) and the achievement in the subject according to gender among the Institut Kemahiran MARA (IKM) Besut students. Besides, the study also focuses on identifying the correlation between students' learning behaviour and their performances in Mathematics. This study involves 236 respondents who are selected randomly among semester two, three and four students of July-December 2009 session which comprised of 198(83.9%) males and 38(16.1%) females. The Mathematics performances are based on the result of the final examination of January-Jun 2009 session. The data was collected through the questionnaire adapted from Arsaythamby (2006) instrument which uses scale four points to gauge behaviour based on interest, motivation and expectation in learning Mathematics. The data were analysed using SPSS version 12.0 which involved frequency, percentage, mean, standard deviation, t-test and Pearson correlation analysis. The findings show that the differentiation does not exist between learning behaviour and Mathematics performances based on gender. The results of the Pearson correlation analysis shows that the significant relationship is exist between students' learning behaviour and their Mathematics performances. The results create awareness to teachers and students that learning behaviour is important in achieving good results. Among steps that can be taken by teachers to generate interest, motivation and expectation among students are by being a likeable teacher, producing interesting lessons and explaining the important of each topic taught. It also helps if the teacher prepares pre-tests to the students before conducting examinations